Evaluación del método químico con ácido sulfúrico para la extracción de goma de tara (caesalpinia spinosa) - Bermeo Macas, Rusbelt Alexander (2021)
Tara is a forest native to the Andean area, it has great potential in agro-export and agro-industry, since it can be used as a raw material for the production of gums, which is characterized by being one of the most demanded by-products on the international market when applied as additive in the Food industry, however, in Ecuador and particularly in the province of Loja, this potencial is not exploited, selling tara as a raw material; taking this in to account, in this investigation developed in the months of September of the 2019 to March 2020, the evaluation of the chemical method with sulfuric acid for the extraction of tara gum (Caesalpinia spinosa) was raised, in order to generate added value to the species, to achieve it, first determined the optimal conditions for the extraction of tara gum by the chemical method whit sulfuric acid, for this 5 tratments with different solubilization times (range of 15 minutes) were performed, to which the physical-chemical and organoleptic characteristics were assessed; in addition, the treatments were analyzed base on the extraction yield of the tara gum, taking in to account that the yield is as high as posible without neglecting the quality of the gum, the results show thar the T3 treatment (solubilization temperatura 80ºC, sulphuric acid concentration 72% and contact time of 60 minutes) has the best gum quality characteristics, in the function of the organoleptic analisys (color, smell and texture); regarding of the extraction yield of the tara gum applying the optimim conditions was achieved 22%. Finally, a manual on the methodology and results obtained was developed with the aim of transferring the knowledge generated to the actors related to the production of the tara.